1977
DOI: 10.1073/pnas.74.8.3335
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of phage phiX174 DNA inactivation by benzo(a)pyrene-7,8-dihydrodiol-9,10-epoxide.

Abstract: A previous report from this laboratory has shown that certain derivatives of polycyclic aromatic hydrocarbons bind to 4X174 DNA and render it noninfectious. The present work describes the relationship between the extent of 4X174 DNA binding by (±) -anti-benzo [alpyrene-7,8-dihydrodiol-9,10- (1-3), it reacts covalently with nucleic acids (4, 5), and DNA conjugated with anti-BPdiolepoxide has been isolated from cultured cells exposed to BP (2, 6). In addition, several studies have shown that BP-diolepoxide is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In developing this in vitro system to measure termination of DNA synthesis at lesions in the DNA, we had two major objectives: to determine whether a particular lesion is a block to synthesis by DNA polymerases, and to be able to detect (5,7,13) have concluded that UV-induced pyrimidine dimers and adducts of BPDE in DNA are blocks to synthesis by pol I and pol III of E. coli. However, none of these systems have been able to eliminate the problem of illegitimate priming; that is, if a DNA template contains multiple 3'-OH termini that can act as primers for DNA polymerase, synthesis may reinitiate downstream from a site of termination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing this in vitro system to measure termination of DNA synthesis at lesions in the DNA, we had two major objectives: to determine whether a particular lesion is a block to synthesis by DNA polymerases, and to be able to detect (5,7,13) have concluded that UV-induced pyrimidine dimers and adducts of BPDE in DNA are blocks to synthesis by pol I and pol III of E. coli. However, none of these systems have been able to eliminate the problem of illegitimate priming; that is, if a DNA template contains multiple 3'-OH termini that can act as primers for DNA polymerase, synthesis may reinitiate downstream from a site of termination.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of pyrimidine dimers or benzo(a)pyrene diolepoxide (BPDE) residues in this template produces an absolute block to synthesis catalyzed by DNA polymerases I and III from E. coli (5,7). On OX174…”
Section: Introductionmentioning
confidence: 99%
“…While the long term effects have been widely studied, much less is known about acute effects of BPDE-DNA adducts in Previous studies indicated a high affinity of the transcripcells. In vitro studies have amply demonstrated that BPDEtion factor Sp1 for DNA adducts derived from benzo[a]-DNA adducts represent strong blocks to the progression of pyrene diol epoxide (BPDE) in sequences that are not both DNA polymerase and RNA polymerase (12)(13)(14)(15). Thus, normal binding sites for Sp1.…”
mentioning
confidence: 99%
“…The ability to use a completely sequenced DNA (Sanger et al 1977) is a major dvantage and both Radmans group (Caillet-Fauquet et al 1977) and group led by S. Weiss at the University of Chicago (Hsu et al 1977) have used X174 DNA to show that a single pyrimidine dimer or a single benzpyrene residue can be an absolute block to DNA synthesis catalyzed by E. coli DNA polymerase.…”
Section: Bypass Mechanismsmentioning
confidence: 99%